HUMANIZATION OF EDUCATION AND INNOVATIVE COMPETENCE - Shodiyev Safar (Journals Park Publishing, 2022)
The article scientifically substantiates the humanization of education and innovative potential. The ideas of humanism, the desire to achieve happiness and justice have long been reflected in folk art, literature, religious, philosophical and pedagogical teachings. Humanitarian education is an education based on the principles of universal values, human life and health, and free development of the individual. The humanization of the education system in Uzbekistan is an integral part of the humanization of society as a whole.
Keywords: person, education, humanization, upbringing, universal values